A Disruptive Force to Challenge the Conventional Female Identity: Victorian Dramatic Monologue - Apaydın Özdemir, Feyza (Journal of History Culture and Art Research, 2023)
This study aims to analyze the use of dramatic monologue in constructing female identity in the poems "Xantippe" by Amy Levy and "Faded" by Augusta Webster. In this sense, this study has dual layers, which aim to complicate the general realisation of the dramatic monologue by focusing on the women poets' monologues having an important place in the tradition of form, and to foreground Victorian women poets’ construction of feminine identity by using the dramatic monologue. The analysis of poems displays that women poets, Augusta Webster and Amy Levy challenged Victorian female identity, which imprisoned women in the Victorian ideal female image, and represented women's identity as free from male identity by violating Victorian gender norms. Thanks to dramatic monologues that provide a large horizon of female characters, from the mythological wife to the old spinster, Levy and Webster question, protest, revise, and criticise societal perception of women and cultural expectations from women. In this way, the analysis of Webster’s and Levy’s dramatic monologues as a medium for constructing female identity allows us to discover the worlds of women under the social pressure of their age, as well. Moreover, while they are exemplifying the new image of women, they are touching on a common issue of all Victorian suppressed women.